Pengaruh Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Karyawan Dimediasi Oleh Organizational Citizenship Behaviour (Studi Pada Karyawan Hotel Aston Inn Pandanaran) - Salsabilla, Salsabilla; Lukiastuti, Fitri; Djou, LD Gadi; Retnosary, Rieke (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to explain the mediating influence of organizational citizenship behavior (OCB) on the relationship between leadership and work motivation on the performance of Aston Inn Semarang hotel employees. This research uses a survey method, with employees as respondents. The population in this study was all employees at Aston Inn Semarang, totaling 50 people. The data used is primary data from distributing questionnaires to employees as respondents. The sampling technique used is saturated sampling, where the sample collection technique uses all members of the population. Data analysis using SmartPLS. The results of this research state that leadership and work motivation have a positive and significant effect on OCB, leadership and work motivation have a positive and significant effect on the performance of hotel employees. OCB has a positive and significant effect on hotel employee performance. OCB is able to mediate the relationship between leadership and hotel employee performance. OCB is unable to mediate the relationship between work motivation and hotel employee performance